Boondoggles, Rent-Seeking, and Political Checks and Balances: Public Investment under Unaccountable Governments - Keefer, Philip; Knack, Stephen (The Review of Economics and Statistics, 2007)
We show that public investment is dramatically higher in countries with low-quality governance and limited political checks and balances or no competitive elections. This result is robust to a number of specifications. The most plausible interpretation of these results is that these governments use public investment as a vehicle to increase their rent-seeking. This evidence suggests that efforts to increase public investment in countries with weak governance, or to measure the growth effects of productive public investment using only observed measures of public investment, should be undertaken with caution.